Analysis of body esteem and social anxiety in late adolescents - Dina Sukma (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Body esteem is how a person evaluates body parts and body functions. Exploitation of the media makes a person tend to judge negatively on his body which affects the occurrence of social anxiety. This study aims to analyze body esteem and its relationship with social anxiety in late adolescents. This research is a quantitative research with correlational descriptive method. The participants were 232 students majoring in Guidance and Counseling Department at Universitas Negeri Padang. The participants were are 42 young male and 190 young female students. Data were collected through the instrument The Body-Esteem Scale and The Social Anxiety Scale. The data is processed by Pearson Correlations. The results showed that there were a relationship between negative body esteem with high social anxiety that occurred in both gender.